THE EFFECT OF AUDITOR EXPERIENCE AND SELF-EFFICACY ON AUDITOR PERFORMANCE AT THE REGIONAL INSPECTORATE OF BONE BOLANGO DISTRICT - Wahyuni Rahman; Sahmin Noholo; Hendra Pratama Danial (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to determine the effect of auditor experience and self-efficacy on auditor performance at the Bone Bolango Regency Inspectorate. This study used a quantitative approach with a causal associative method. Data were collected by distributing questionnaires to 38 respondents selected using a census sampling technique (total sampling). Data analysis techniques included classical assumption tests, multiple linear regression analysis, and hypothesis testing (t-tests and F-tests) using Statistical Package for the Social Sciences (SPSS) version 26 software. The results indicate that, partially, auditor experience has no significant effect on auditor performance, while self-efficacy has a positive and significant effect on auditor performance. Simultaneously, auditor experience and self-efficacy have a significant effect on auditor performance. The coefficient of determination indicates that 73.1% of the variation in auditor performance can be explained by auditor experience and self-efficacy, while the remaining 26.9% is influenced by factors outside the research model.